Therapeutic ketogenic diet as treatment for anorexia nervosa - Frank, Guido K. W.; Scolnick, Barbara (Frontiers in Nutrition, 2024)
Anorexia nervosa (AN) is a severe psychiatric disorder. However, we lack neurobiological models and interventions to explain and treat the core characteristics of food restriction, feeling fat, and body size overestimation. Research has made progress in understanding brain function involved in the pathophysiology of AN, but translating those results into biological therapies has been challenging. Studies have suggested that metabolic factors could contribute to developing and maintaining AN pathophysiology. Here, we describe a neurobiological model for why using a therapeutic ketogenic diet could address key alterations in brain function in AN and prevent the desire for weight loss and associated eating disorder-specific symptoms. This translational model is based on animal studies and human data and integrates behavioral traits, brain neural energy metabolism, and neurotransmitter function. Pilot data indicate that the intervention can dramatically reduce eating and body-related fears, although larger studies across illness stages still need to be conducted.